2015
DOI: 10.2527/jas.2013-6883
|View full text |Cite
|
Sign up to set email alerts
|

The effects of deoxynivalenol-contaminated corn dried distillers grains with solubles in nursery pig diets and potential for mitigation by commercially available feed additives

Abstract: Four experiments were conducted to investigate the effects of deoxynivalenol (DON) from naturally contaminated dried distillers grains with solubles (DDGS) and the efficacy of feed additives in nursery pig diets. In Exp. 1, 180 pigs (10.3 ± 0.2 kg BW) were fed 1 of 5 diets for 21 d. Diets were 1) Positive Control (PC; < 0.5 mg/kg DON), 2) Negative Control (NC; 4 mg/kg DON), 3) NC + 0.10% Biofix (Biomin Inc., Herzogenburg, Austria), 4) NC + 0.15% Cel-can (VAST Inc., Mason City, IA) and 0.50% bentonite clay, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…In several growth studies, overall G:F was not affected by DON exposure (Friend et al, 1984;Pollman et al, 1985;Grosjean et al, 2002). Nonetheless, when reported by phase, pigs regularly have poorer G:F during the initial period (Pollman et al, 1985; Frobose et al, 2015). This is consistent with the poorer G:F reported in experiments with shorter durations (5 to 9 d; He et al, 1993;Li et al, 2011).…”
Section: Discussionsupporting
confidence: 83%
“…In several growth studies, overall G:F was not affected by DON exposure (Friend et al, 1984;Pollman et al, 1985;Grosjean et al, 2002). Nonetheless, when reported by phase, pigs regularly have poorer G:F during the initial period (Pollman et al, 1985; Frobose et al, 2015). This is consistent with the poorer G:F reported in experiments with shorter durations (5 to 9 d; He et al, 1993;Li et al, 2011).…”
Section: Discussionsupporting
confidence: 83%
“…Long-term exposure to DON-contaminated feed is known to worsen feed efficiency in grow-finish swine (Bergsjo et al, 1993;Dänicke et al, 2004b;Patience et al, 2014), but in a series of 4 nursery pig experiments, Frobose et al (2015) consistently observed depressed feed efficiency only during the initial 3 to 7 d of DON-contaminated diet consumption, consistent with the reduction in G:F observed only during d 0 to 7 in the present growth study. This transitory depression in G:F may be partly attributed to wasted feed from pigs sorting due to taste aversion.…”
Section: Growth Experimentssupporting
confidence: 86%
“…Before the experiment, basal diet was added to the DON-contaminated diet to reach a DON content of 4 mg/kg diet. The concentration of DON was chosen according to previous studies [19,20]. The synthesis of BCU was based on a previous study [16,17].…”
Section: Preparation Of Don-contaminated Feed and Bcumentioning
confidence: 99%